La formation du regard clinique - Yvonne Wübben (Revue d’Histoire des Sciences Humaines)
The article investigates the function of textbooks for the formation of clinical psychiatry in German speaking countries from 1875-1900. It argues that textbooks were supposed to play a crucial epistemic role for directing clinical observation. For this reason psychiatrists like Emil Kraepelin devoted much time and effort to writing and rewriting textbooks. Their rhetoric can be linked to différents nosological positions and practises of case writing.